Medico-Legal Aspects of Sexual Assault Accuracy and limitations of Forensic Evidence in Sexual Assault Cases - Abdullah, Iffat Imtiaz Iffi, Fida Hussain, Farhat Sultana, Abdul Waheed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Sexual assault remains one of the most underreported and complex medico-legal challenges worldwide. The accurate detection and interpretation of forensic evidence play a pivotal role in substantiating allegations, guiding legal proceedings, and delivering justice. However, the effectiveness of forensic evidence can be influenced by several factors including the timing of examination, the condition of the victim, the availability of trained professionals, and procedural limitations. Objective: To evaluate the accuracy and limitations of forensic evidence in medico-legal sexual assault cases and assess the relationship between evidence recovery, injury documentation, and time to examination. Methods: This descriptive cross-sectional study was conducted at the Department of Forensic Medicine, Bacha Khan Medical College Mardan, and Allama Iqbal Medical College Lahore, Pakistan, from January 2022 to March 2023. A total of 70 medico-legal cases of alleged sexual assault were reviewed. Data were extracted on demographic details, time of presentation, types of forensic evidence collected, presence of physical injuries, and DNA test outcomes. Descriptive statistics were used to analyze the data. Results: The majority of victims were females (75.7%), with adolescents (13–18 years) representing the most affected group. A significant portion of cases (54.3%) presented within 24 hours of assault. Semen was detected in 44.3% of cases, spermatozoa in 32.9%, and a DNA match with the alleged perpetrator was found in 37.1% of cases. Genital injuries were present in 41.4% of victims. However, 55.7% of cases showed no biological evidence, often due to delayed reporting, hygiene measures, or procedural errors. Conclusion: While forensic evidence can significantly aid in the investigation of sexual assault cases, it has inherent limitations. Early examination, proper evidence collection, and multidisciplinary collaboration are critical for maximizing the utility of forensic findings. A victim-centered, evidence-informed, and context-sensitive approach is essential for ensuring justice in sexual assault investigations. Keywords: Sexual assault, forensic evidence, medico-legal, DNA analysis, injury documentation, limitations.